The Influence of Compensation and Work Environment towards Teacherâs Job Satisfaction - Rahayuningsih, Sri (SHAHIH: Journal of Islamicate Multidisciplinary, 2017)
This study focus on the teacher satisfaction and work style based on the compensation given. This study aims; (1) to know the effect of compensation towards teachersâ work satisfaction, (2) to know the effect of work environment towards teachersâ work satisfaction, (3) to know the effect ofÂ  compensation and work environment simultaneouslyÂ  towards teachersâ work satisfaction. The data analysis used in this research were descriptive analysis, pre-requirement test analysis, and hypothesis test including simple linier regression analysis that was used to know the effect of compensation towards teachersâ work satisfaction and the effect of work environment towards teachersâ work satisfaction and multiple regression analysis to know the effect of compensation and work environment simultaneouslyÂ  towards teachersâ work satisfaction. Â From the hypothesis testing, it is found that; (1) there was a positive effect of compensation towards teachersâ work satisfaction which revealed by Y=55.501 + 0.585 X1 with the correlation coefficient as 0.834 with contribution about 0.695 or 6905%, (2) ) there is a positive effect of work environment towards teachersâ work satisfaction which revealed by Y=56.157 + 0.585 X2 with the correlation coefficient as 0.740 with contribution about 0.547 or 54.7%, (3) there is a positive effect ofÂ  compensation and work environment simultaneouslyÂ  towards teachersâ work satisfaction which revealed by Y=39.414 + 0.427 X1 + 0.299 X2 with the correlation coefficient as 0.887 with contribution about 0.788 or 78.8%.To increase teachersâ work satisfaction, there must be the increase of compensation as the appreciation for teachersâ performance. Besides, a conducive work environment must be increased to increase teachersâ work satisfaction which will contribute to the increase of education quality